Strategizing Beyond the State: The Global Environmental Movement and Corporate Actors - Edge, Jessica L. (My University, 2011)
Due to the political, economic, and technological changes brought on by the processes of globalization, since the mid-1990s, civil society groups have increasingly chosen to target corporate actors. This thesis focuses on the circumstances under which civil society groups have chosen to target corporate actors in addition to and instead of states. How corporate actors respond to activist demands and the factors that shape how they approach corporate social responsibility and the environment are also examined. This thesis uses a political economic opportunity structure approach to understand the relationship between civil society groups and corporate actors. While activist networks are increasingly targeting corporate actors, they also continue to target the state to achieve their objectives. This two prong strategy has been effective for activist networks because it allows them to take advantage of weaknesses found in both political and industry opportunity structures. However, while the impact of activist networks is shaped by the structural environment in which they operate, activist networks also create new opportunities through the strategic use of frames and tactics to draw attention to and create support for the issues with which they are concerned. Two case studies involving the global environmental movement and corporate actors are examined in this thesis. The first case study focuses on a global network of activists opposed to genetically modified organisms (GMOs) and the network’s interactions with states and a variety of corporations in their campaign to prevent the introduction of GMOs into the environment. The second case study examines the activities of a network of activists concerned about the environmental impacts of electronic waste (the e-waste network). The e-waste network sought to ensure the proper disposal of electronic waste and increase the sustainability of the electronics industry through the targeting of states and corporations.
Keywords: civil society; global governance; electronic waste; genetically modified organisms; corporate actors; corporate campaigns; International Relations; International Relations